KONTRIBUSI MUSIK KLASIK SEBAGAI IRINGAN TARIAN BALLET DI ROYAL BALLET CENTRE MEDAN - Johana Teresia Purba (Grenek: Jurnal Seni Musik, 2018)
This study aims to find out the background of the use of classical music as Ballet dance accompaniment, whatever classical music title used as Ballet dance accompanist, and how the contribution of classical music as Ballet dance accompaniment.This research is based on a theoretical explanation of the meaning of contribution, classical music, music accompaniment and Ballet dance. This research was conducted in September 2017 until November 2017. This research uses Qualitative Descriptive method, which become population and sample in this research is Ballet students at Intermedite level at Royal Ballet Center Medan. This research takes place on Jl. General Ahmad Yani No 104 A Medan. The data were collected by observation, interview, visual / drawing / documentation, literature study and triangeles.The results of this study indicate that the contribution of classical music as Ballet dance accompaniment that is as one motion of relaxation, motion confirmation, atmosphere builder, trigger memory and as an illustration. Classical music contributes greatly to Ballet dance accompaniment. When performing the initial stage or heating the music used is Le Cygne. Movement is done at this stage is the plie movement, then in the second stage or core of the music used is Swan Lake, then the move is done Swan Lake dance that resembles the movement of swans, movements performed in accordance with the classical music used